Health Behavior Study in Natural Disaster Vulnerability in Palu City (Case Study of Tondo Huntap, Palu City) - Arwan Arwan; Sadly Syam; Muhammad Zikra; Firmansyah Firmansyah; Muhammad Sabri Syahrir; Muhammad Aji Satria (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Background: The strengthening of health behavior intentions in disaster mitigation poses an urgent challenge to be addressed. There is a need to enhance health behavior preparedness in facing disaster threats, considering that the city of Palu is located in an earthquake-prone zone and has a history of being affected by earthquakes. This research aims to study health behavior and mental health in relation to disaster vulnerability, based on a case study of Huntap in the Tondo area, Palu City, Central Sulawesi, using the Theory of Planned Behavior (TPB) approach. Method: The type of research used is a mixed-method approach with a sequential explanatory model. Data collection utilizes questionnaires and observation sheets, supplemented by interview methods in the qualitative approach. Result: This study shows that the chi-square test results indicate a significant relationship between attitude, subjective norms, behavioral control, and mental health (<0.05) with health behavior. Meanwhile, in-depth interviews revealed barriers to health behavior, such as respondents' attitudes towards preparedness efforts and inadequate access to information and health workers. There is a pressing need for mental health interventions to improve preparedness. Moreover, there is a need for mental health interventions to improve mental health in promoting disaster preparedness efforts. Conclusion: This study concludes that mental health related to disaster vulnerability among the Huntap Tondo community is still lacking, which will impact disaster preparedness. Mental health interventions are essential to enhance preparedness and reduce disaster-related losses. Therefore, mental health interventions are needed to enhance preparedness for disasters and take action to reduce disaster losses and damage.